Celiac disease and human gut microbiota – how can we study the composition of microorganisms? - Szczuciński, Wiktor; Salamon, Dominika; Sopel, Anna; Gosiewski, Tomasz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2025)
Celiac disease is an autoimmune disorder induced by consumption of gluten protein present in foods such as wheat and rye. In recent years there has been increasing evidence that changes in composition of gut microbiota may play a significant role in the pathogenesis of celiac disease. Multiple methods of bacterial identification may be used to find microbiota changes characteristic for celiac disease, and the latest methods such as next generation sequencing offer new possibilities of detecting previously unknown bacterial groups that may play a role in the occurrence of celiac disease. This review focuses on multiple methods of identifying bacterial gut microbiome and presents results of recent studies exploring the link between gut microbiota composition and celiac disease..